MODEL KOMUNIKASI PROGRAM CSR “GAMBUT LESTARI DAN MASYARAKAT MANDIRI” PT KPI RU II PRODUKSI SUNGAI PAKNING - Sumiati Sumiati; Welly Wirman; Anuar Rasyid (Komitmen: Jurnal Ilmiah Manajemen, 2022)
This study aims to analyze the communication model of the Peat Lestari CSR program and the Independent Community at PT KPI RU II, which is produced by Sungai Pakning. This study uses a qualitative descriptive approach. The technique of determining the informant is purposive. Data collection techniques using interviews, observation and documentation. Data analysis techniques use the concept of Miles and Huberman. And data validation techniques use extended participation and triangulation. The results of the study show that the Peat Lestari and Mandiri Community CSR programs use the donuts communication model. This model is to provide a starting point for improving communication in CSR programs. This suggests that there is a positive potential among corporates from organized message management. With a participatory and persuasive communication approach, it can make communication flexible. So that there will be a match of perceptions. DCM is an upgrade from traditional or ordinary communication. This communication is able to realize an interactive process. The purpose of traditional or ordinary communication is that the convergence communication model (social media) is changed to an oral communication model.